The effectiveness of anti-corruption policies: measuring the impact of anti-corruption policies on integrity in the public organizations of South Korea - Min, Kyoung-sun (Crime, law and social change, 2019)
To confront their struggles with corruption, many countries have adopted various anti-corruption policies. Do anti-corruption policies reduce corruption? Experts in this field have developed anti-corruption measures, and yet the current literature stops short of evaluating the effectiveness of anti-corruption tools due to a lack of data. Using the Anti-Corruption Initiative Assessment data and the Integrity Assessment data, this paper empirically tests the effectiveness of anti-corruption policies on the level of integrity amongst 183 public organizations in South Korea from 2013 to 2016. To capture the impacts of anti-corruption policies, this article employs a fixed effects model and time-lagged regression. A case study is presented to illustrate some interesting points that are related to the findings. This paper finds that the implementation of anti-corruption policies has a positive effect on the level of integrity in the public organizations. This result counters the conventional argument that we have failed to reduce corruption. In South Korea at least, the success of anti-corruption policies is not elusive. Corruption can be curbed when anti-corruption policies are vigorously implemented.